2010
DOI: 10.1155/2010/376095
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between healthy and tumor tissues on formalin-fixed paraffin-embedded breast cancer samples using IR imaging

Abstract: Abstract. This work presents a pilot study to illustrate the potential of Fourier transform infrared (FT-IR) imaging in breast cancer research. Using this technique, we have acquired infrared (IR) microspectroscopic images from healthy and cancerous breast tissue section from one patient. First of all, a Student t-test was applied, showing DNA/RNA spectral region (1400-1000 cm −1 ) as the most discriminant for the differentiation between healthy and tumor samples. Afterwards, a supervised pattern recognition m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…One approach that might play a role in the identification of tumor cells is Fourier transform infrared (FTIR) spectroscopic imaging. 4,5 Recent reports have been largely dominated by studies focusing on FTIR spectroscopic imaging to characterize skin tumors, 6 tumor cells in brain tissue, 5,7 breast tissue, 8 in the colon, 9 and many others. The high sensitivity of the method enables to identify tumors even in a very early stage of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…One approach that might play a role in the identification of tumor cells is Fourier transform infrared (FTIR) spectroscopic imaging. 4,5 Recent reports have been largely dominated by studies focusing on FTIR spectroscopic imaging to characterize skin tumors, 6 tumor cells in brain tissue, 5,7 breast tissue, 8 in the colon, 9 and many others. The high sensitivity of the method enables to identify tumors even in a very early stage of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since N-H and C=O stretches were major absorption peaks along with C-H stretch which appears at frequency of: N-H stretch appears at 3 Spectra of Group II also showed bands for N-H, C=O and C-H stretch. Spectra of group III showed that the intensity of transmittance for C-H was reduced and N-H, C=O bands were weak.…”
Section: Resultsmentioning
confidence: 94%
“…Several diagnostic methods are currently in use. The most common method used by pathologists is the microscopic inspection of tissue in order to obtain morphological data [2,3] . This effect is caused by biochemical changes to the metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…This spatial resolution was long believed to be the best possible, and led to promising initial results in IR imaging and breast cancer research [2][3][4][5][6][7] , but can make it difficult or impossible to distinguish certain cell types in breast tissue, limiting the usefulness of the technique for histopathology. Recent work with 2.7 μm image pixels 8 hinted at the advantage of increased definition in IR imaging, but pixel binning and low NA prevented adequate sampling 9 and the full utilization of the increased magnification.…”
Section: Hd Ft-irmentioning
confidence: 99%